SCHOOL LIFE AND COMMUNITY ECONOMIC CHALLENGE: A NEWFOUNDLAND CASE STUDY - Fowler, Ken (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
This study explored changes in student attitudes toward school life following the 1992 Newfoundland groundfishery closure. Using data extracted from a provincial quality of school life (QSL) survey, means associated with students from a sample of fishing communities were compared with provincial means. Although community students had poorer perceptions of school life both before and during the fishery closure, more positive attitudes were evident after the closure, suggesting that parental job loss may have motivated children to aspire beyond their parents’ vocational achievements. However, not all communities demonstrated such a positive change. Plausible explanations for the community variability are discussed. Key words: economic crisis, quality of school life, student attitudes, fishing communities Cette étude porte sur les attitudes des élèves à l’endroit de la vie à l’école après la fermeture de la pêche de fond à Terre‐Neuve en 1992. À l’aide de données tirées d’un sondage provincial sur la qualité de la vie à l’école, des moyennes associées à des élèves provenant d’un échantillon de villages de pêcheurs ont été comparées à des moyennes provinciales. Malgré le fait que les élèves de ces villages avaient de moins bonnes perceptions de la vie à l’école avant et pendant la fermeture de la pêche de fond, des attitudes plus positives étaient manifestes après la fermeture, ce qui donne à penser que la perte d’emploi de leurs parents peut avoir inciter les enfants à vouloir faire autre chose dans la vie que leurs parents. Le changement n’a pas été vécu d’une manière aussi positive par toutes les collectivités. L’auteur fournit des explications plausibles à ces variations. Mots clés : crise économique, qualité de la vie à l’école, attitudes des élèves, villages de pêcheurs